2004
DOI: 10.1212/01.wnl.0000134664.80320.92
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of donepezil in mild cognitive impairment

Abstract: Although significant treatment effects were not seen in the primary efficacy measures, outcomes on secondary measures suggest promising directions for further evaluation of donepezil treatment in patients with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(217 citation statements)
references
References 35 publications
7
206
2
2
Order By: Relevance
“…In the following decade, these drugs were tested for AD prevention in randomized controlled trials (RCTs). Trials involved subjects with mild cognitive impairment (MCI) and showed possible positive effects on some but not all primary endpoints for donepezil [27][28][29] and rivastigmine [30]. However, to date, cholinesterase inhibitors are not approved for prevention.…”
Section: Ad-specific Drugsmentioning
confidence: 99%
“…In the following decade, these drugs were tested for AD prevention in randomized controlled trials (RCTs). Trials involved subjects with mild cognitive impairment (MCI) and showed possible positive effects on some but not all primary endpoints for donepezil [27][28][29] and rivastigmine [30]. However, to date, cholinesterase inhibitors are not approved for prevention.…”
Section: Ad-specific Drugsmentioning
confidence: 99%
“…[16] focused more on short-term symptomatic effects. In this 24-week randomized double-blind placebo-controlled trial, cognitive functioning using the ADAS-Cog and various declarative memory tasks were investigated in 269 patients.…”
Section: Pharmacological Treatment Of MCImentioning
confidence: 99%
“…MCI selection criteria and the overall results from the clinical trial have been reported. 8 Final determination of cognitive status was made by a board-certified psychiatrist (P.M.D.) with expertise in geriatric psychiatry.…”
Section: Subjectsmentioning
confidence: 99%
“…Selection and dosing criteria were as specified for the trial. 8 Neuropsychological assessment consisted of the following tests: Clinical Dementia Rating, MiniMental State Examination (MMSE), Alzheimer Disease Assessment Scale-Cognitive Subscale (ADAS-Cog), New York University Paragraph Test Delayed Recall, Verbal Fluency, Boston Naming Test, Digit Symbol, Digit Span Backward, and Number Cancellation. As such, this was a pilot study, and the sample size was determined by the logistics of recruitment as well as by prior positron-emission tomography and fMRI studies of drug effects.…”
Section: Subjectsmentioning
confidence: 99%